Evaluation of RT-PCR for the Detection of Influenza Virus Serotype H9N2 among Broiler Chickens in Pakistan - Siddique, Naila; Naeem, Khalid; Ahmed, Zaheer; Malik, Salman Akbar (International Journal of Poultry Science, 2008)
A Reverse Transcriptase Polymerase Chain Reaction (RT-PCR) was standardized and compared with virus isolation techniques for the detection of avian influenza virus serotype H9N2 among Broilers suffering from respiratory tract infection. In this regard 50 tissues and cloacal swabs were tested for the isolation of avian influenza viruses. Out of this, 17 samples from tissues and 3 from cloacal swabs showed the presence of AIV H9N2 through virus isolation test while six tissue samples showed the presence of NDV. Out of the negative samples another 15 samples were positive for AIV H9N2 when tested by RT-PCR while seven samples were positive for NDV by RT PCR. Detection of AIV from the cloacal swabs by RT-PCR also confirmed the shedding of AIV among the infected flocks. Apart from detecting the presence of AIV H9N2 from clinical specimens, the RT-PCR was able to detect higher number of AIV, from healthy flocks, which would otherwise have been missed by routine lab methods or wrongly diagnosed and treated adversely.